Hypoxia-inducible Factor Regulates Ten-eleven Translocated Methylcytosine Dioxygenase 1-c-Myc Binding Involved in Depression-like Behavior in Prenatal Hypoxia Offspring. (15th October 2022) - Zeng, Hongtao; Wei, Bin; Liu, Jingliu; Lu, Likui; Li, Lingjun; Wang, Bin; Sun, Miao
Highlights: Prenatal hypoxia leads to depression-like behavior in male offspring. Hif-1α regulates Tet1-c-Myc binding involved in depression-like behavior in offspring exposed to prenatal hypoxia. The competitive relationship between Hif-1α and c-Myc for Tet1 may bring new ideas for the treatment of depression. Abstract: Prenatal hypoxia (PH) is one of the most common adverse stimulation during pregnancy. The brain is fragile in the fetal period and sensitive to hypoxia. The offspring who have experienced PH may be at increased risk of developing neurodevelopmental disorders after birth and various neuropsychiatric diseases after adulthood. In this study, pregnant mice used to generate PH offspring were treated with hypoxia (10.5% oxygen) from gestational day 12.5–17.5. Compared with control mice, the birth weight of offspring in the PH group was significantly lower and the male adult offspring exhibited significant depression-like behavior. The expression of the oxygen-sensitive subunit of hypoxia-inducible factor (Hif-1α) was significantly elevated, whereas Ten-eleven translocated methylcytosine dioxygenase 1 (Tet1) and c-Myc, which is closely related to cell proliferation, were significantly decreased in the hippocampus of the male offspring in the PH group. In addition, the PH group showed increased binding of Hif-1α to Tet1, and decreased binding of Tet1 to c-Myc, resulting in increased ubiquitinated degradation of c-Myc and decreased neurogenesis in the hippocampus of the male offspring. These findings suggest that Hif-1α regulates Tet1-c-Myc binding involved in depression-like behavior in PH offspring and Hif-1α can be used as a detection index of stress-related diseases.